The Structural Planning of Bunda Halimah Hospital Universitas Batam Using Steel Frame Construction - Edi Indera (Natural Sciences Engineering and Technology Journal, 2023)
The structural planning of the Bunda Halimah Hospital Universitas Batam uses steel frame construction, planning includes calculating the load acting on the structure, namely in the form of dead loads, living loads, not taking into account earthquake loads. The height of the column in the planning of the Structure of the Bunda Halimah Hospital, is as high as 23.5 m. The process of analyzing the planning of building structures using the ETABS program. Guided by the Indonesian Steel Building Loading Regulations 1984 and SNI steel, to analyze the calculation of the dimensions of columns, beams and plates. The results of the loading calculation based on the Indonesian Steel Building Planning Regulations of 1984 were obtained for this building using WF 250x250x9x14kg/m child beams, WF Main Beams 300x300x10x15kg/m, WF building columns 350x350x12x19 kg/m, and using concrete plates for roofs with a thickness of 100 mm of D8 – 200 mm reinforcement and concrete plates for floors with a thickness of 120 mm of D8 - 200 mm reinforcement.